Pengaruh Tangibles, Empathy, Reliability, Responsiveness dan Assurance Jasa Kesehatan Terhadap Kepuasan Pasien Pengguna BPJS pada Puskesmas Sungai Sariak Kabupaten Padang Pariaman - Alfadila Hasan (Universitas Batanghari Jambi, 2021)
This study aims to analyze: The Effect of Tangibles, Empathy, Reliability, Responsiveness and Assurance on Patient Satisfaction. This type of research is descriptive and associative research. The population and sample of this study were all patients who came for treatment at Sungai Sariak Public Health Center in Padang Pariaman Regency who used BPJS as many as 96 people. The instrument used for the study was a closed questionnaire. Data analysis techniques are descriptive analysis and inductive analysis: classic assumption test, model feasibility test and path analysis test. The results showed that: 1) tangibles had a significant effect on patient satisfaction. 2) empathy has a significant effect on patient satisfaction. 3) reliability of patient satisfaction. 4) responsiveness has a significant effect on patient satisfaction. 5) assurance has a significant effect on patient satisfaction. It is recommended to Sungai Sariak Puskesmas Padang Pariaman Regency to provide quality services to all patients without any difference in social status so that patients do not feel any difference to go to the Sungai Sariak Puskesmas.